Revealing the Microscopic Mechanism of Elementary Vortex Pinning in Superconductors - C. Chen; Y. Liu; Y. Chen; Y. N. Hu; T. Z. Zhang; D. Li; X. Wang; C. X. Wang; Z. Y. W. Lu; Y. H. Zhang; Q. L. Zhang; X. L. Dong; et al. (Physical Review X)
Vortex pinning is a crucial factor that determines the critical current of practical superconductors and enables their diverse applications. However, the underlying mechanism of vortex pinning has long been elusive, lacking a clear microscopic explanation. Here, using high-resolution scanning tunneling microscopy, we studied single vortex pinning induced by point defect in layered FeSe-based superconductors. We found the defect-vortex interaction drives low-energy vortex bound states away from E_{F}, creating a “mini” gap that effectively lowers the system energy and enhances pinning. By measuring the local density of states, we directly obtained the elementary pinning energy and estimated the pinning force via the spatial gradient of pinning energy. The results are consistent with bulk critical current measurement. Furthermore, we showed that a general microscopic quantum model incorporating defect-vortex interaction can naturally capture our observation. It suggests that the local pairing near pinned vortex core is actually enhanced compared to unpinned vortex, which is beyond the traditional understanding that nonsuperconducting regions pin vortices. Our study thus unveils a general microscopic mechanism of vortex pinning in superconductors and provides insights for enhancing the critical current of practical superconductors.